Immunologic characteristics of HIV-infected individuals who make broadly neutralizing antibodies - Borrow, P; Moody, M (Wiley, 2017)
Induction of broadly neutralising antibodies (bnAbs) capable of inhibiting infection with diverse variants of human immunodeficiency virus type 1 (HIV-1) is a key, as-yet-unachieved goal of prophylactic HIV-1 vaccine strategies. However some HIV-infected individuals develop bnAbs after ~2-4 years of infection, enabling analysis of features of these antibodies and the immunological environment that enables their induction. Distinct subsets of CD4+ T cells play opposing roles in the regulation of humoral responses: T follicular helper (Tfh) cells support germinal centre formation and provide help for affinity maturation and the development of memory B cells and plasma cells, whilst regulatory CD4+ (Treg) cells including T follicular regulatory (Tfr) cells inhibit the germinal centre reaction to limit autoantibody production. BnAbs exhibit high somatic mutation frequencies, long third heavy chain complementarity determining regions and/or autoreactivity, suggesting that bnAb generation is likely to be highly dependent on the activity of CD4+ Tfh cells, and may be constrained by host tolerance controls. This review discusses what is known about the immunological environment during HIV-1 infection, in particular alterations in CD4+ Tfh, Treg and Tfr populations and autoantibody generation, and how this is related to bnAb development, and considers the implications for HIV-1 vaccine design.